2020
DOI: 10.7150/jca.43561
|View full text |Cite
|
Sign up to set email alerts
|

High Fat High Calories Diet (HFD) Increase Gut Susceptibility to Carcinogens by Altering the Gut Microbial Community

Abstract: Objective: To investigate the risk of colorectal cancer and its relationship with colonic flora and microenvironment under high-fat and high-calorie diet. Methods: Wistar rats were used to study, and they were given normal diet, high-fat diet, and dimethyl hydrazine (DMH) to induce the occurrence of colorectal cancer. Then observe the difference in tumor formation and the relationship among microbial community, inflammatory factors and metabolism. Results: No tumors were found in the normal diet group (G1) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 21 publications
(21 reference statements)
1
23
0
Order By: Relevance
“…Increase of Clostridium XVIII is reported in various pro-inflammatory and pathological conditions, as in gastric cancer patients in the perioperative period [22] or in those with high fat diets [23]. Its increase in CDI has been sporadically reported [20], but this taxon is not commonly listed as associated with CDI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase of Clostridium XVIII is reported in various pro-inflammatory and pathological conditions, as in gastric cancer patients in the perioperative period [22] or in those with high fat diets [23]. Its increase in CDI has been sporadically reported [20], but this taxon is not commonly listed as associated with CDI.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of Clostridium XVIII are controversial, as some species produce exotoxins and have a pro-inflammatory potential, while other act as probiotics [ 21 ]. Increase of Clostridium XVIII is reported in various pro-inflammatory and pathological conditions, as in gastric cancer patients in the perioperative period [ 22 ] or in those with high fat diets [ 23 ]. Its increase in CDI has been sporadically reported [ 20 ], but this taxon is not commonly listed as associated with CDI.…”
Section: Discussionmentioning
confidence: 99%
“…Animal feeding as our previous report [2]. Feed is cobalt 60 radiation-sterilized pellets for rats and mice (Nanjing Jiangning Qinglongshan feed Company), high-fat feed (formulation: 20 g lard, 5 g cholesterol, 10 g Tween 80, add water to 50 ml).…”
Section: Methodsmentioning
confidence: 99%
“…Peyman et al [14] studies had showed that p-Cymene has anti-inflammatory properties. Our previous study has found that HFD increase gut susceptibility to carcinogens by altering the gut microbial community [2]. However, up to now, its anti-tumor and antioxidation mechanism of P-cymene is still unclear.…”
Section: Ivyspringmentioning
confidence: 97%
See 1 more Smart Citation